Microalbuminuria, Kidney Function, and Daily Physical Activity - Baris Afsar (International Journal of Nephrology)
The present study was carried out to investigate independent relationship between daily physical activity, microalbuminuria, and kidney function. The demographic characteristics and laboratory parameters were recorded for all patients. The determination of daily activities was carried out by Nottingham Extended Activities of Daily Living Scale (NEADLS) which was performed for each patient in an interview. Totally 139 patients were enrolled. In the whole group NEADLS score was correlated with age (rho: −0.759, P<0.0001), clinical systolic blood pressure (rho: −0.212, P: 0.018), blood urea nitrogen (rho: −0.516, P<0.0001), creatinine (rho: −0.501, P<0.0001), uric acid (rho: −0.308, P<0.0001), albumin (rho: 0.382, P<0.0001), total cholesterol (rho: −0.194, P: 0.022), LDL-cholesterol (rho: −0.230, P: 0.008), hemoglobin (rho: 0.256, P: 0.002), creatinine clearance (rho: 0.565, P<0.0001), 24-hour urinary protein excretion (rho: −0.324, P<0.0001), and 24-hour urinary albumin excretion (UAE) (rho: −0.483, P<0.0001). The multivariate linear regression of independent factors corelated with logarithmically converted NEADLS score (as a dependent variable) has shown that age (P<0.0001), presence of coronary artery disease (P: 0.011), hemoglobin (P: 0.020), 24-hour creatinine clearance (P: 0.004), and 24-hour urinary albumin excretion (P<0.0001) were independently corelated with NEADLS score. In conclusion, both UAE and kidney function were independently associated with daily physical activity.